PENERAPAN METODE TERJEMAH DALAM PEMBELAJARAN BAHASA ARAB DI MADRAH ALIYAH SUKOREJO SITUBONDO - Edy Sulaiman (LP2M IAI Miftahul Ulum Pamekasan, 2017)
Arabic is the main language for Muslims in communicating, either with goals or with others, in addition to using other languages. This is because the teachings of all Islamic religions are in Arabic which must be understood and understood by its adherents. Because of the importance of this language, Arabic is used as one of the subjects of Islamic learning. Therefore, the implementation of teaching cannot be separated from the constraints or educational components that can produce good quality. Referring to the above in this study the researcher raised the problem of